# math

posted by .

find the indicated outputs for f(x)=3x^2-4x
f(0)=
f(-1)=
f(2)=

• math -

f ( 0 ) = 3 * 0 ^ 2 - 4 * 0 = 3 * 0 + 0 = 0 + 0 = 0

f ( - 1 ) = 3 * ( - 1 ) ^ 2 - 4 * ( - 1 ) = 3 * 1 + 4 = 3 + 4 = 7

f ( 2 ) = 3 * 2 ^ 2 - 4 * 2 = 3 * 4 - 4 * 2 = 12 - 8 = 4

## Similar Questions

1. ### Math

Find the indicated outputs for f(x)=5x^2-2x. f(0)= f(-1)= f(2)=
2. ### Math

Find the indicated outputs for f(x)= 5x^2-2x The 2 after the ^ is an exponent. f(0)=0 f(-1)= f(2)=
3. ### math

can someone check this please find indicated outputs for f(x)= 4x^2 - 2x f(0)=0 f(-1)=6 f(2)=14
4. ### Math

Find the indicated outputs for f(x)= 5x^2-5x. F(0) = 0 f(-1)= 1 f(2)= 45 is this right?
5. ### math

can someone help me I am not understandng how to do this; Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) <P>indicated outputs 2 <P>F(x) = 4x - 5x
6. ### math

Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated outputs 2 F(x) = 4x - 5x I need help with these can anyone help?
7. ### Algebra

Find the indicated outputs for f(x)= 5 x(2) - 4x. F(0)= f(-1)= f(2)=
8. ### algebra

find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=
9. ### algebra

Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)
10. ### algebra

Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)

More Similar Questions